1999
DOI: 10.1111/j.1600-065x.1999.tb01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide vaccines as probes of antibody repertoires in man

Abstract: Antibodies specific for capsular polysaccharide epitopes mediate immunity to encapsulated bacterial pathogens, and accordingly, vaccine development has focused upon the induction of these specificities. Efficacious vaccines, consisting of either polysaccharide alone or polysaccharide coupled to protein carriers, have been developed for a number of pathogens. Their clinical importance notwithstanding, these vaccines serve as model antigens to study the genetic and somatic forces molding adaptive immunity in man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 76 publications
1
43
0
Order By: Relevance
“…These results do not necessarily follow from oligoclonality itself and, given the combinatorial diversity available to the immune system, it is quite remarkable that such a limited diversity is seen between individuals. A similar recurrence in gene usage is seen in the response to Hib PS, where most individuals utilize an A2 L chain paired with a VH3-23 H chain to form Hib PS-specific Fabs (16). It has been suggested that the high-molecular-weight capsular polysaccharides, which are polymers of smaller repeating subunits, lack epitope diversity and that this results in the observed oligoclonality of the response.…”
Section: Discussionmentioning
confidence: 70%
“…These results do not necessarily follow from oligoclonality itself and, given the combinatorial diversity available to the immune system, it is quite remarkable that such a limited diversity is seen between individuals. A similar recurrence in gene usage is seen in the response to Hib PS, where most individuals utilize an A2 L chain paired with a VH3-23 H chain to form Hib PS-specific Fabs (16). It has been suggested that the high-molecular-weight capsular polysaccharides, which are polymers of smaller repeating subunits, lack epitope diversity and that this results in the observed oligoclonality of the response.…”
Section: Discussionmentioning
confidence: 70%
“…The Fab pair 14-3-14-4 and Fab 23F-1 used HV 3-23, but their CDR-3s were distinctive, and they paired with different L chains. This promiscuity of HV 3-23 is perhaps not too surprising in light of the fact that this gene segment is commonly expressed in the peripheral repertoire (61), is used by a plethora of Abs having reactivities with either self or foreign Ags (47), and is a prominent member of the Hib PS repertoire, where it pairs with the KV 2D-29 V region to form the canonical combining site (37,48). Table 3 summarizes our Fab results and the results of previous studies of V region gene segment usage by PPSspecific monoclonal Abs (MAbs).…”
Section: Discussionmentioning
confidence: 99%
“…26 Children under the age of 2 y are unable to make an efficient immune response to T-independent antigens such as plain polysaccharide vaccines. This phenomenon is not well understood but present models suggest (1) an immaturity of most B cells, e.g., lack of CD21/complement receptor 2 on neonatal B cells, [27][28][29] (2) differences in activation requirements between primary and secondary B cells with young children having primary B cells that require both BCR signaling and T cell help for activation, 30 (3) low frequency of marginal zone B cells, 31,32 (4) lower levels of complement C3, and (5) immaturity of marginal zone dendritic cells and the marginal zone in young children. 33 Although there are no data in infants, B MEM responses to plain polysaccharide and glycoconjugate vaccines have been compared when given to adolescents and adults.…”
Section: -Valent Pneumococcal Polysaccharide Vaccine (Ppv-23)mentioning
confidence: 99%